2006
DOI: 10.1007/s11515-006-0004-0
|View full text |Cite
|
Sign up to set email alerts
|

Masking effect of different durations of forward masker sound on acoustical responses of mouse inferior collicular neurons to probe sound

Abstract: To study the effects of different durations of forward masker sound on neuronal firing and rate-intensity function (RIF) of mouse inferior collicular (IC) neurons, a tone relative to 5 dB above the minimum threshold (re MT+5 dB) of the best frequency of recorded neurons was used as forward masker sound under free field stimulation condition. The masker durations used were 40, 60, 80, and 100 ms. Results showed that as masker duration was increased, inhibition in neuronal firing was enhanced (P < 0.000 1, n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…A sound-elicited suppressive aftereffect in the IC similar to that revealed by the present study was reported by previous papers ( Park and Pollak, 1993 ; Covey et al, 1996 ; Finlayson and Adam, 1997 ; Litovsky and Yin, 1998a , b ; Faure et al, 2003 ; Mei et al, 2006 ; Nelson et al, 2009 ; Singheiser et al, 2012 ). Despite similarities, quantitative differences existed among different studies in the time course of suppression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A sound-elicited suppressive aftereffect in the IC similar to that revealed by the present study was reported by previous papers ( Park and Pollak, 1993 ; Covey et al, 1996 ; Finlayson and Adam, 1997 ; Litovsky and Yin, 1998a , b ; Faure et al, 2003 ; Mei et al, 2006 ; Nelson et al, 2009 ; Singheiser et al, 2012 ). Despite similarities, quantitative differences existed among different studies in the time course of suppression.…”
Section: Discussionsupporting
confidence: 92%
“…Action-potential firing elicited by a tone burst at a neuron’s characteristic frequency (CF, the frequency at which the threshold of response is the lowest) is suppressed by another tone burst at a different frequency. When two sounds are temporally separated, the response to a trailing sound can be suppressed by a leading sound with the degree of suppression being dependent on the time gap between the sounds ( Finlayson and Adam, 1997 ; Faure et al, 2003 ; Mei et al, 2006 ; Nelson et al, 2009 ; Zhang and Kelly, 2009 ; Singheiser et al, 2012 ; Gai, 2016 ). When two simultaneously presented sounds are spatially separated, the response to a sound with a fixed location can be suppressed by a relocated sound, with the effect being dependent on the angle of separation ( Ratnam and Feng, 1998 ; Lane and Delgutte, 2005 ; Day et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…If the gap is undetectably close between sounds, it will generate the masking effect [55,111]. Offset responses are considered to play the role in gap detection, and gap detection not only depends on gap duration but also especially on pre-gap duration (i.e.…”
Section: Gap Detectionmentioning
confidence: 99%